Experiencing the Sublime — The Contributions of Akka Mahadevi - Srivastava, Gouri (THE PRIMARY TEACHER, 2016)
This paper discusses the significant contributions of women — writers, philosophers, saints and philanthropists. The paper is a biographical account to understand the works and preaching of Akka Mahadevi, a twelfth century woman saint poet of Karnataka who practised Shaivism. Her poetry instills a sense of bhakti, coupled with her feminist instincts, and an unconventional life that she lived